FLUXES AND SOURCES OF VOLATILES DISCHARGED FROM KUDRYAVY, A SUBDUCTION ZONE VOLCANO, KURILE ISLANDS - Fischer T.P.; Williams S.N.; Giggenbach W.F.; Sano Y. (My University, 1998)
The Kudryavy volcano, a 996-m-high basaltic-andesite cone on the northeastern shore of Iturup Island in the Kuriles, erupted last in 1883 and has since been in a persistent state of high-temperature, >900°C fumarolic activity. Its flux of SO2, measured by COSPEC, is 73±15 t/d, or 416 Mmol/a. In combination with the chemical composition of the parent gas supplying the high-temperature vents and the isotopic compositions of He and C, it allows the evaluation of contributions from major source components, such as the mantle, the crust, and subducted sediments and carbonate. The 3He/4He ratio of 6.7 RA corresponds to a 84% mantle origin and a flux of 2200 mol/a of mantle He. At a He concentration of 2200 mol/Mt, the mass of mantle material required to generate this flux is 1.0 Mt/a. The same mass produces a flux of 0.025 mol/a of 3He and of 50 Mmol/a of mantle CO2 at a CO2/3He ratio of 2·109. In conjunction with the C-isotopic composition of fumarolic CO2 of −7.2‰, about 12% of the CO2 are derived from the mantle, 67% from marine carbonate in subducted, altered oceanic crust, 21% are of subducted organic sedimentary origin. The flux of 280 Mmol/a of carbonate-derived CO2 requires 0.41 Mt/a of oceanic crust with a CO2 content of 3 wt%, and 0.35 Mt/a of sedimentary material to supply the organic CO2 flux of 86 Mmol/a. Nitrogen from the mantle contributes at most 2% to the total N2 flux of 5.4 Mmol/a. Assuming N to be derived from the subducted sediments, its concentration there is 460 mg/kg. The total volume of mantle and subducted material required to maintain the flux of volatiles over the 100 a period of high-temperature fumarolic activity of Kudryavy is 0.07 km3. Steady-state release of volatiles from the depth of arc magma generation to the fumaroles and continuously high heat flow from the mantle are proposed as the main process supporting the long-term high-temperature degassing at Kudryavy. In this steady-state system, the calculated volatile fluxes are balanced over time by volatiles originating from subducted sediments, hydrothermally altered oceanic crust below the Kudryavy volcano and the mantle wedge. This has significant implications for volatile cycling from the Earth's crust and mantle to the atmosphere.